The Development of System Monitoring and Evaluation of Research Output and Community Service (SIMONEL) - R. Alit; Sugiarto (Future Science)
Information systems are currently needed by various companies in the world. Even more, Information systems provide convenience in helping companies to obtain desired target. This information system can also assist in Output Data Management Research and Community Service. In this case the research is conducted at LPPM (Institution Research and Community Service) In making this system, RAD (Rapid Application Development) method is used. This method is almost similar to the Waterfall method but the work done is faster.Because users and researchers copy work together in making this information systemimplementation, this application uses the Codeigniter Framework and MySQL as database. In making this information system, it is expected to facilitate lecturers in the UPN